Formation and phase evolution of liquid phase-separated metallic glasses with double glass transition, crystallization and melting. (September 2016) - Qin, Y.S.; Shi, Y.; Han, X.L.; Song, K.K.; Cao, C.D.; Li, X.L.; Wang, S.H.; He, J.; Wang, L.; Kaban, I.; Eckert, J.
Graphical abstract: Highlights: Intrinsic and extrinsic effects on the formation of phase-separated alloys under different casting conditions were analyzed. Compositional dependence of the glass-forming ability of the present phase separated alloys were studied. The present phase separated metallic glasses exhibit double glass transition, crystallization and melting during heating. Abstract: Zr57 Co27 Al16 and La57 Co27 Al16 alloys with excellent glass-forming ability (GFA) were adopted to synthesize new phase-separated bulk metallic glasses (BMGs) upon rapid solidification. (Zrx La1 − x )57 Co27 Al16 (x = 0.2, 0.4, 0.6, and 0.8) melts separate into ZrCo-rich and La-rich liquids upon cooling due to the existence of a miscibility gap in Zr-La liquids. The intrinsic and extrinsic mechanisms for the formation of phase-separated alloys under different casting conditions were analyzed in detail. The GFA of the studied alloys changes in the following order: Zr57 Co27 Al16 > La57 Co27 Al16 > Zr11.4 La45.6 Co27 Al16 > Zr22.8 La34.2 Co27 Al16 > Zr34.2 La22.8 Co27 Al16 > Zr45.6 La11.4 Co27 Al16 . The quaternary Zr-La-Co-Al phase-separated metallic glasses (MGs) are shown to experience double glass transition, crystallization and melting events, which could be regarded as possible model materials to study the glassy transition and structural relaxation behavior of BMGs.